Pengaruh Penggunaan Sistem Informasi Loyverse Pos Terhadap Kepercayaan Atasan Di Warkop Wafkopi - Risna; Fidyani (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study aims to analyze the effect of using the Loyverse Point of Sale (POS) Information System on the level of trust among supervisors at Warkop Wafkopi. The development of information technology requires business actors, including MSMEs, to adopt accurate transaction recording systems to increase transparency and minimize fraud. Loyverse POS is a digital cashier system that provides features for sales recording, inventory, financial reports, and real-time transaction monitoring. This study uses a quantitative method with a survey approach by distributing questionnaires to employees and management of Warkop Wafkopi. The data were analyzed using simple linear regression to see the extent of the influence of using Loyverse POS on the variable of supervisor trust. The results show that the use of Loyverse POS has a positive and significant effect on increasing supervisor trust. These findings imply that the digitization of sales systems can be an important tool in building trust and improving the effectiveness of supervision in small and medium-sized enterprises.